The Prevalence of LUTS in Men Aged ≥40 years based on the IPSS-Ina Questionnaire - Wangga P. Lasandara; Muhammad Taufiqurrachman; Dimas Bintoro Kresna Yustisia Handoyo (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2023)
Objectives. LUTS (Lower Urinary Tract Symptoms) are several symptoms experienced by a person due to various pathologies that occur in the lower urinary tract. The prevalence of LUTS in ≥ 40-year-old men is high and many methods including IPSS have been made to measure LUTS. Unfortunately, the high prevalence is not followed by the number of patients who are seeking treatment for their LUTS.Methods. This observational cross-sectional study used 45 men aged ≥40 years who came to Tongauna Health Center. Each respondent was asked to fill out the IPSS questionnaire. Moreover, when the respondent has LUTS, he is also asked if he is ever looking for health care providers, where he consultations, and what the reason is if he is never looking for it.Result. Of 45 men, there are 37 men who have LUTS and only 8 asymptomatic men. Mild LUTS is the most common symptom with 22 respondents, followed by moderate with 11 respondents, and only 4 respondents who suffered from severe LUTS. Pleased (1) is the most respondent’s feel for their Quality of Life score. Only 7 respondents are ever looking for treatment, and the common reasons for them not getting treatment are their misperception about LUTS, economic factors, and attitude toward their illness.Conclusion. The number of LUTS patients≥40 years old male at Tongauna District is high, but their initiative to treat this symptom is still low due to many factors like knowledge, economic, and patient attitude.